Feasibility study of full waveform inversion of Love-SH waves for detecting small-scale shallow anomalies - Xu Sun; Wei Xu; Yingju Xiong; Yong Li; Xiaoqing Song (AIP Advances)
In engineering surveys, conventional SH-wave seismic exploration methods exhibit limited resolution for detecting small-scale shallow anomalies, often failing to meet practical requirements. Seismic full waveform inversion (FWI), a high-resolution imaging technique, is based on waveform fitting and utilizes the complete waveform information of seismic records to invert subsurface medium parameters precisely. This study explores the feasibility of employing Love-SH wave FWI to enhance the detection of small-scale shallow anomalies. First, the theoretical methodology of SH-wave FWI is introduced, followed by the development of a theoretical model designed to assess its resolution ability for small-scale geological anomalies. Theoretical analysis and numerical experiments indicate that the Love-SH wave FWI method demonstrates strong resolution capabilities for small-scale anomalies near the surface, and compared to Rayleigh-PSV wave FWI, Love-SH wave FWI exhibits less parameter crosstalk and lower inversion nonlinearity, facilitating easier convergence to a global minimum.